Pobreza das mulheres chefes de família da Região Nordeste do Brasil: uma análise multidimensional - Oliveira, Nadja Simone Menezes Nery de (2018)
The objective of this research is to analyze the poverty feminization process in the Northeast´s Brazilian region, from 2004 to 2015, through a multidimensional approach. For this purpose, was estimated the Multidimensional Poverty Index (MPI) by using the microdata of the National Household Sample Survey (PNAD) for the years 2004 to 2015. the poverty incidence results (H) showed that in Brazil the proportion of poor female heads of household was lower than the male proportion. In 2004, the percentage of poor women who were heads of their families was 55.03%; by 2015, the percentage of poor women fell to 39.31%. The intensity of poverty or average poverty (A) in 2004 revealed that these women presented, on average, 20.07% deprivations of the total indicators considered, which corresponded to 7 of the 37 indicators. In 2015, this proportion represented 18.53%, which means that these women presented on average deprivations in approximately 7 of the 37 indicators. The results of the incidence of adjusted poverty (M0), revealed that in 2004 about 11.05% of Brazilian women were multidimensionally poor, in 2015 the percentage of women in this condition fell to 7.28%. In the Northeast region, unlike that observed for female Brazilian heads of household, it was possible to verify that women in this region are multidimensionally poorer than men, and to confirm the poverty feminization process occurrence in this Region, since poverty in this Region declined more among men than among women. It was also observed that for the female heads of families in the Northeast Region, the dimensions of access to work, availability of resources and consumption of goods were those in which women were more vulnerable in all the years of the analyzed period. In 2015, approximately 53.34%, 48.04% and 34.52% of these women were deprived in these dimensions, respectively. In comparison to male heads of household in the Northeast Region, women were more deprived in terms of family vulnerability, availability of resources until the year 2011, and from the year 2009 on the use of time. There was also a noticeable decrease in multidimensional poverty for female heads of households in the Northeast, whose MPI for the eleven year period has been reduced by 29.65% while the same indicator for female heads of household in Brazil was reduced and 34,12%. The dimensions related to work and income were the ones that contributed the most to the insertion of northeastern women into a condition of poverty and are thus subjects that require more attention from the public power, since the verified distance in the percentage of deprivations observed in these dimensions in relation to Brazil was significant.